Critical Dialogue to Open Doors for Leadership. Issue 160 (1st November 2018) - Blom, Andrew; Johnson, Matthew R.
Abstract: This chapter explores how the high‐impact practice of critical, intergroup dialogue connects leadership with the broader learning objectives in the liberal arts. Based on experiences with building partnerships for leadership learning at their own university, the authors offer lessons for fostering cross‐unit collaboration.